Gender-Based Anxiety Disorders and Mental Health in Nepal - Sharma, Tilak Prasad (Curriculum Development Journal, 2024)
Anxiety and depression illnesses are getting more and more common around the world and gender inequality is a major factor behind these diseases. This paper, analyze the gendered anxiety disorders common in Nepal through the lens of the 2022 NDHS data set. Under a cross-sectional research design involving 14,280 households, in both urban and rural households. The assessment of anxiety was done using the Generalized Anxiety Disorder scale (GAD-7), which shows that females aged between 15-24 years are more affected, with 20.5 among the youth. Women across all severity of socio-demographic factors are found to be more anxious than men. The work also reveals that the vulnerable and excluded population, the Dalit and the Madhesi, are the leading victims of the phenomenon. This explains how gender based discrimination works with other structural factors arising from feudalism, capitalism, and socioeconomic, cultural, and environmental settings. Rural-living woman in the lowest wealth quintile has higher odds of depression compared to their male counterparts. More over the rationale for mental health policies should directly address and engage with, the economic and societal oppression enshrined in patriarchal and capitalist systems. Such interventions should be wide to correct social injustice and ensure equal access to mental health services, especially for women of color. Implementing a focused Programme, which encompasses socio economic and gender-sensitive changes and incorporating these into mental health Battings could help reduce mental health loads and bring social and economic transformation.